Probing the Universe using Pulsar Timing Arrays - Falxa Mikel (EPJ Web of Conferences)
Supermassive black holes (SMBH), found at the centers of galaxies, have been observed in the early Universe, yet their rapid growth remains an open question. When SMBHs form binary systems during galaxy mergers, they are expected to emit strong gravitational waves (GW). A large population of such binaries would produce a stochastic gravitational wave background (GWB), detectable through perturbations in the timing of millisecond pulsars. In 2023, Pulsar Timing Array (PTA) collaborations reported evidence for a GW signal in their datasets, with the most plausible explanation being a population of SMBH binaries, although other cosmological sources cannot be ruled out. This paper reviews the current understanding of SMBH formation and growth, introduces the PTA method for detecting GWs, and discusses the interpretations of the 2023 results. The results provide promising evidence for the presence of a GWB, offering new insights into SMBH binaries and opening avenues for further exploration of the early universe.